A high-frequency transimpedance amplifier for CMOS integrated 2D CMUT array towards 3D ultrasound imaging - Huang, Xiwei (2013)
One transimpedance amplifier based CMOS analog front-end (AFE) receiver is integrated with capacitive micromachined ultrasound transducers (CMUTs) towards high frequency 3D ultrasound imaging. Considering device specifications from CMUTs, the TIA is designed to amplify received signals from 17.5MHz to 52.5MHz with center frequency at 35MHz; and is fabricated in Global Foundry 0.18-μm 30-V high-voltage (HV) Bipolar/CMOS/DMOS (BCD) process. The measurement results show that the TIA with power-supply 6V can reach transimpedance gain of 61dBΩ and operating frequency from 17.5MHz to 100MHz. The measured input referred noise is 27.5pA/√Hz. Acoustic pulse-echo testing is conducted to demonstrate the receiving functionality of the designed 3D ultrasound imaging system.